2021
DOI: 10.3390/ani11051245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fermented Products Produced by Bacillus licheniformis on the Growth Performance and Cecal Microbial Community of Broilers under Coccidial Challenge

Abstract: This study investigated the effects of fermented products produced by Bacillus licheniformis (fermented products) on the growth performance and cecal microbial community in broilers exposed to coccidial challenge. A total of 108 one-day-old male broiler chicks (Ross 308) were randomly allotted to one of three treatments. Each treatment was distributed into six replicate cages with six birds each. The treatments consisted of a basal diet without treatment (NC), basal diet plus coccidial challenge (PC), and basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…BLFP can alleviate C. perfringens -induced necrotic enteritis in broilers [ 15 ]. Furthermore, BLFP supplementation modulates gut-microbiota composition and exhibits anti-coccidial activity in broilers exposed to mixed coccidia infection [ 26 ]. In the current study, we further demonstrated that 1.25 g/kg BLFP improved survival rate, reduced cecal-lesion scores, and increased anti-coccidial index in broilers exposed to E. tenella challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BLFP can alleviate C. perfringens -induced necrotic enteritis in broilers [ 15 ]. Furthermore, BLFP supplementation modulates gut-microbiota composition and exhibits anti-coccidial activity in broilers exposed to mixed coccidia infection [ 26 ]. In the current study, we further demonstrated that 1.25 g/kg BLFP improved survival rate, reduced cecal-lesion scores, and increased anti-coccidial index in broilers exposed to E. tenella challenge.…”
Section: Discussionmentioning
confidence: 99%
“…For oocyst-count index (OI), feces from two broilers per replicate were freshly collected daily in a separate cage from days 21 to 35 and pooled. Oocysts per gram of feces was determined via the McMaster’s counting technique, and OI was calculated according to previously described methods [ 26 ]. Timeline of sampling during the entire experiment is shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…B. licheniformis is widely used in industry, horticulture and pharmacy. It is a promising producer of enzymes, platform chemicals [ 28 , 29 , 30 ], antibiotics [ 31 , 32 ] and EPSs with antimicrobial, antioxidant and anticancer activities [ 33 , 34 ]. That is why the species is commonly used in the biocontrol of plant diseases [ 35 ] and the development of probiotics [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…One ducks per replicate were chosen at the end of the experiment (day 85) based on their average weight and then euthanized using carbon dioxide inhalation (birds chosen for microbiota analysis were identical to those for LSI analysis) ( Cheng et al, 2021 ); the contents of duck cecal were collected from each duck. Then quickly frozen in liquid nitrogen, sent to the laboratory and stored at −80°C for further analysis of microbiota and metabolites.…”
Section: Methodsmentioning
confidence: 99%
“…B. licheniformis is widely used in industry, horticulture, and pharmacy. It is a promising producer of enzymes, platform chemicals ( Petrova et al, 2020 ), antibiotics ( Cheng et al, 2021 ), and EPSs with antimicrobial, antioxidant, and anticancer activities ( Xu et al, 2019 ; Petrova et al, 2021 ; Vinothkanna et al, 2021 ). Probiotics are widely regarded as one of the most effective alternatives to antibiotics because they maintain or restore normal microbiome, inhibit pathogen adhesion to intestinal wall, prevent inflammation, and protect intestinal barrier function ( Van Baarlen et al, 2013 ; Cisek and Binek, 2014 ; Gresse et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%